Qur’anic Sociopreneurship Conception Through Interpretation of Q.S. Al-Rūm/30: 33-42 - Achyar Zein; Nawir Yuslem; Khoiruddin Hasibuan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
There is no novelty in the interpretation or the interrelation of Q.S. al-Rūm/30:33-42, since the time of the Salaf to the Commentators today. Their interpretation seems to be repeated. Therefore, this paper seeks to discuss the interpretation of Q.S. al-Rūm/30:33-42, using the interrelation (munāsabah) approach, which in essence, has implications for the explanation of the Qur’anic sociopreneurship conception. This paper can be classified as library research with a qualitative descriptive approach. The interpretations of previous commentators still guide this paper as to the basis for interpreting the Qur’anic sociopreneurship conception. Thus it can be said that this paper is a continuation of the previous interpretations of Q.S. al- Rūm/30:33-42. This paper will describe interrelation Q.S. al-Rūm/30:33-42, which are divided into two parts. First, the interrelation between Q.S. al-Rūm/30:39 with Q.S. al-Rūm/30:38 and Q.S. al-Rūm/30:40. Second, the interrelation between Q.S. al-Rūm/30:39 with Q.S. al-Rūm/30:33-37 and Q.S. al-Rūm/30:41-42.